Tibial implant fixation in TKA worth a revision?—how to avoid stress-shielding even for stiff metallic implants. Issue 3 (17th February 2021) - Eidel, B.; Gote, A.; Fritzen, C.-P.; Ohrndorf, A.; Christ, H.-J.
Abstract: In total knee arthroplasty (TKA), force is transmitted into the tibia by a combined plate-stem device along with cemented or cementless stem fixation. The present work analyzes this force transmission in finite element simulations with the main aim to avoid reported postsurgical bone density reduction as a consequence of a reduced tibial bone loading. In the numerical analysis different implant materials, stem/extension lengths and implant-to-stem interface conditions are considered, from a stiff fully cemented fixation to sliding contact conditions with a low friction coefficient. The impact of these variations on bone loading changes are measured by (i) decomposing the total force into parts mediated by the plate and by the stem and by (ii) post-surgery strain energy density (SED) deviations. Based on a bionics-inspired perspective on how nature in pre-operative conditions carries out force transfer from the knee joint into the tibia, a modified implant–bone interface is suggested that alters force transmission towards physiological conditions while preserving the geometries of the standard plate-stem endoprosthesis design. The key aspect is that the axial force is predominantly transmitted through the plate into proximal bone which requires a compliant bone-stem interface as realized by sliding friction conditions at a low friction coefficient. These interface conditions avoid stress shielding almost completely, preserve pre-surgery bone loading such that bone resorption is not likely to occur.